Examining the Link between Word of Mouth and Brand Equity: A Study on International Fast Food Restaurants in Malaysia - Hanaysha, Jalal (Journal of Asian Business Strategy, 2016)
This paper aims to test the link between word of mouth and brand equity in the restaurant industry. The data were collected from293 customers of the international fast food restaurants in east coast Malaysia using convenience sampling technique. The collected data were analysed using SPSS and Structural Equation Modelling (SEM). The findings revealed that word of mouth has a significant relationship with brand image and brand loyalty. Furthermore, word of mouth has a significant relationship with brand preference and brand leadership. Finally, the findings indicated that word of mouth has a significant positive relationship with overall brand equity. This paper provides useful implications for the decision makers in the fast food restaurants by improving their understanding of the role of word of mouth in affecting brand equity.